2008
DOI: 10.3736/jcim20080907
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ginsenoside Rg1 on expression of insulin-like growth factor-1 in brain of rats with brain contusion

Abstract: Ginsenoside Rg1 enhances the recovery of the contused brain through increasing the expression of IGF-1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The molecular components responsible for ginseng's actions are ginsenosides (28,29), which are triterpene saponins that have a rigid steroidal skeleton with sugar moieties (30,31). Among the ginsenosides, Rg1 is the most abundant and is the active ingredient of P. ginseng (32,33). Previous studies have shown Rg1 to be a functional ligand of GR (34)(35)(36).…”
mentioning
confidence: 99%
“…The molecular components responsible for ginseng's actions are ginsenosides (28,29), which are triterpene saponins that have a rigid steroidal skeleton with sugar moieties (30,31). Among the ginsenosides, Rg1 is the most abundant and is the active ingredient of P. ginseng (32,33). Previous studies have shown Rg1 to be a functional ligand of GR (34)(35)(36).…”
mentioning
confidence: 99%
“…Ginsenoside Rg1 can inhibit lipid peroxidation in the brain [33], improve the learning ability and memory function of rats [34], improve the spatial learning ability, reduce the size of infarction area, promote Functional recovery of brain tissue [35]. By activating Na+ and K+ ATP enzyme within synaptic corpuscle of mouse [36], Rg1 can increase the concentration of cyclic adenosine monophosphate in the hippocampus [37].…”
Section: Ginsenoside-rg1mentioning
confidence: 99%
“…thus, improve spatial learning ability [50]. Rg1 can promote brain functional recovery [51], inhibit calcium accumulation, reduce potassium loss [52], reduce neuronal and cell apoptotic death by increasing the expression of Insulin-like growth factor One (IGF-1) in the brain [53]. Rg-1 can increase neuronal survival, reduce the release of LDH, reduce the morphological changes of cells and the division of nuclear DNA.…”
Section: Ginsenoside-rg1mentioning
confidence: 99%